Precise measurement of the top quark mass in the dilepton channel at D0 - Abazov, V. M. (2011)
We measure the top quark mass (mt) in pp̄ collisions at a center of mass energy √s=1.96TeV using dilepton tt̄→W +bW-b̄→+νb -ν̄b̄ events, where denotes an electron, a muon, or a tau that decays leptonically. The data correspond to an integrated luminosity of 5.4fb-1 collected with the D0 detector at the Fermilab Tevatron Collider. We obtain mt=174.0±1.8(stat)±2. 4(syst)GeV, which is in agreement with the current world average m t=173.3±1.1GeV. This is currently the most precise measurement of mt in the dilepton channel. © 2011 American Physical Society.